Discovery of Several Novel Targets that Enhance β-Carotene Production in Saccharomyces cerevisiae - Li, Jia; Shen, Jia; Sun, Zhiqiang; Li, Jing; Li, Changfu; Li, Xiaohua; Zhang, Yansheng (Frontiers in Microbiology, 2017)
β-Carotene is the precursor of vitamin A, and also exhibits multiple pharmaceutical functions by itself. In comparison to chemical synthesis, the production of β-carotene in microbes by metabolic engineering strategy is relatively inexpensive. Identifying genes enhancing β-carotene production in microbes is important for engineering a strain of producing higher yields of β-carotene. Most of previous efforts in identifying the gene targets have focused on the isoprenoid pathway where the β-carotene biosynthesis belongs. However, due to the complex interactions between metabolic fluxes, seemingly irrelevant genes that are outside the isoprenoid pathway might also affect β-carotene biosynthesis. To this end, here we provided an example that several novel gene targets, which are outside the isoprenoid pathway, have improving effects on β-carotene synthesis in yeast cells, when they were over-expressed. Among these targets, the class E protein of the vacuolar protein-sorting pathway (Did2) led to the highest improvement in β-carotene yields, which was 2.1-fold to that of the corresponding control. This improvement was further explained by the observation that the overexpression of the DID2 gene generally boosted the transcriptions of β-carotene pathway genes. The mechanism by which the other targets improve the production of β-carotene is discussed.